(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Primary objective from conducting this case study is to underline the role of nonlinguistic factors such as age, sex, personality, learning styles and strategies in learning second language and take the advantage of differentiated instruction to assist them to fill the gaps they have. For example, as an introvert learner I have always wondered to know why I always struggle to prosper as a fluent speaker, while some other learners in the same class with me sound rather fluent are making less effort even though we are being taught by one teacher, studying similar books we are all in the same atmosphere. Through carrying out this research I would like to reveal what distinguish them from each other to succeed in any aspects of the language and as an upcoming teacher how can I help them to bridge the gaps to make some noticeable improvements.